Numerical Modeling of LiteSteel Beams Subject to Shear - Keerthan, Poologanathan; Mahendran, Mahen (Journal of structural engineering (New York, N.Y.), 2011)
A LiteSteel beam (LSB) is a new cold-formed steel hollow flange channel beam produced by using a patented manufacturing process involving simultaneous cold-forming and dual electric resistance welding. It has the beneficial characteristics of torsionally rigid closed rectangular flanges combined with the economical fabrication processes from a single strip of high-strength steel. Although the LSB sections are commonly used as flexural members, no research has been conducted on the shear behavior of LSBs. Therefore, experimental and numerical studies were conducted to investigate the shear behavior and strength of LSBs. In this research, finite-element models of LSBs were developed to investigate their nonlinear shear behavior, including their buckling characteristics and ultimate shear strength. They were validated by comparing their results with available experimental results. The models provided full details of the shear buckling and strength characteristics of LSBs and showed the presence of considerable improvements to web shear buckling in LSBs and associated postbuckling strength. This paper presents the details of the finite-element models of LSBs and the results. Both the finite-element analysis (FEA) and experimental results showed that the current design rules in cold-formed steel codes are very conservative for the shear design of LSBs. The ultimate shear capacities from FEAs confirmed the accuracy of proposed shear strength equations for LSBs on the basis of the North American specification and direct strength method (DSM) design equations. Developed finite-element models were used to investigate the reduction to shear capacity of LSBs when full-height web side plates were not used or when only one web side plate was used, and these results are also presented in this paper.